The Association of Household Food Insecurity and the Risk of Calcium Oxalate Stones - Shafi, Hamid; Dorosty Motlagh, Ahmad-Reza; Bagherniya, Mohammad; Daeezadeh, Atefeh; Safarian, Mohammad (Urology Journal, 2017)
Purpose: Food insecurity has been defined as ‘limited or uncertain availability of nutritionally adequate and safe foods’, which associated with adverse health consequences in human. Another alarming condition, which is related to several comorbidities is kidney stone. This study aimed to determine the association of household food insecurity and developing kidney stones (calcium oxalate) in adults referred to medical centers of Babol. Materials and Methods: This case-control study included 200 participants 18-65 years of ages (100 cases, 100 controls). An 18-items food insecurity questionnaire (USDA), a valid and reliable 147-item food frequency questionnaire (FFQ) and demographic characteristics were obtained via interviewing. Results: Sixty eight percent of cases and 40% of controls were food insecure, respectively. Food insecurity was significantly associated with the risk of kidney stone (P < .05). Furthermore, body mass index (BMI) and family history of kidney stone were significantly associated with the risk of kidney stones (P < .05). Conclusion: Food insecurity and BMI were significantly associated with the kidney stone, which shows the importance of availability of nutritionally adequate and safe foods in prevention of the kidney stone.